Self-powered tunable photodetection via flexoelectric engineering of single-phase 2HMoS2 - Junxi Yu; Yuan Zhang; Songjie Yang; Chunlin Song; Shiyao Xu; Boyuan Huang; Qingyuan Wang; Jiangyu Li (Journal of Materiomics, 2025)
Two-dimensional (2D) molybdenum disulfide (MoS2) has shown considerable potential for photodetection, yet existing MoS2-based photodetectors require either external voltage bias or complex heterojunctions. In this work, we present a new device concept based on flexoelectric engineering of bulk photovoltaic effect (BPVE) of 2HMoS2, simplifying the device configuration considerably while enhancing its self-powered photodetection performance. By introducing a strain gradient in the suspended 2HMoS2, we break its inversion symmetry, resulting in BPVE in the otherwise centrosymmetric system. The significant flexoelectric polarization induced also facilitates efficient photocarrier separation, leading to a 41-fold enhancement in short-circuit photocurrent under a strain gradient of 0.95μm−1. Furthermore, the flexoelectric-engineered photodetector can be dynamically tuned via air pressure, enabling multilevel photoconductance and achieving a responsivity of 191 mA/W. This performance surpasses existing self-powered MoS2-based photodetectors reported in literature, offering a strategy for enhanced photodetection.